How to make the ally of inland fisheries and inland aquaculture: A review. Issue 1 (April 2021) - Ma'ruf, I; Kamal, M M; Satria, A; Sulistiono,
Abstract: Inland fisheries are a significant sector especially for those living in villages as a source of both nutritious yet affordable food and the community's income. The increasing pressure on inland fisheries causes a reduction in the amount and size of fish caught as well as the rarity of some species of fish. One measure taken to intensify inland fisheries is by implementing inland aquaculture. Unlike any other controlled condition aquaculture, inland aquaculture is done with adjustment to the water condition. This study aims to describe characteristics of several inland waters of Ogan Komering Ilir regency, South Sumatera Province, Indonesia in particular as well as to provide a guideline for inland aquaculture based on the characteristics of the waters. The description is done by reviewing a number of academic journals and publications which are verified by academics and expert judgment. The main points in describing inland fisheries are water typology, fish resource, water quality, and social community characteristics. After analyzing the inputs from inland fishery characteristics based on the 4 main points previously mentioned, a guideline is created for conducting fish farming in terms of farming methods, seed selection, seed stocking criteria, and institutional arrangement in fish ownership issue.